2012
DOI: 10.1038/ijo.2012.97
|View full text |Cite
|
Sign up to set email alerts
|

An indoline-derived compound that markedly reduces mouse body weight

Abstract: We hypothesize that indoline-derived drug-induced chronic toxicity to the hepatic system leads to a reduction in white adipose tissue mass. The mice adapt to this drug-induced toxicity with reduced steady-state body weight. Understanding molecular mechanisms underlying these responses has potential to identify novel targets for prevention and treatment of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
2
0
Order By: Relevance
“… [5] In another study, an indoline‐derived compound was reported that could markedly reduce body weight and lower the blood sugar level in mouse models. [6] The indoline structure is widely found in natural compounds and has been widely reported as the focus of drug design in recent years. When it is structurally modified to join the indoline moiety in a fused or bonded form, new varieties with powerful pharmacological properties are usually produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… [5] In another study, an indoline‐derived compound was reported that could markedly reduce body weight and lower the blood sugar level in mouse models. [6] The indoline structure is widely found in natural compounds and has been widely reported as the focus of drug design in recent years. When it is structurally modified to join the indoline moiety in a fused or bonded form, new varieties with powerful pharmacological properties are usually produced.…”
Section: Introductionmentioning
confidence: 99%
“…High cholesterol in blood is one of the main causes of cardiovascular diseases, such as atherosclerosis, while the novel indoline derivatives as cholesterol ester protein (CETP) inhibitors was synthesized and showed the powerful effect of reducing cholesterol in blood [5] . In another study, an indoline‐derived compound was reported that could markedly reduce body weight and lower the blood sugar level in mouse models [6] . The indoline structure is widely found in natural compounds and has been widely reported as the focus of drug design in recent years.…”
Section: Introductionmentioning
confidence: 99%